Indigenous Voices at the Musée de la Civilisation in Quebec City - Laurence Desmarais; Laurent Jérôme (Recherches amérindiennes au Québec, 2018)
This article discusses the Indigenous points of view regarding the process in creating the permanent exhibit It’s our Story: First Nations and Inuit of the XXIst Century (2013 - ongoing) at the Musée de la Civilisation in Quebec City. The process was carried out through an extensive consultation with Indigenous communities in Québec following the establishment of special consultative committees and a partnership with the Indigenous organization La Boîte Rouge VIF. The result of this complex process was lauded in the museum world. But did it truly achieve the desired reconciliation between Indigenous Peoples and museums? The article puts forward the perspectives of some Indigenous people on both the creative process and the resulting exhibit, as well as documenting the power play among the people involved. By presenting these Indigenous perspectives at different moments and levels of the development of the exhibit, the article reports on the deficiencies in the desired collaborative process and uncovers the power imbalance that nevertheless was preserved within the museum’s institution, to the detriment of its Indigenous collaborators. Cet article rend compte de points de vue autochtones sur le processus de réalisation de l’exposition permanente du Musée de la civilisation de Québec C’est notre histoire : Premières Nations et Inuit du xxie siècle (2013, en cours) et son résultat. Ce processus a été mené grâce un vaste terrain de concertation dans les communautés autochtones au Québec, après la mise sur pied de comités consultatifs et d’un partenariat privilégié avec l’organisme autochtone La Boîte Rouge VIF. Le résultat de ce processus complexe a été salué et reconnu dans le monde muséal. Mais cette feuille de route a-t-elle réellement participé à la réconciliation entre peuples autochtones et Musées ? L’article propose de valoriser le regard de certains autochtones engagés dans le processus de réalisation de l’exposition et de documenter les rapports qui se sont construits et négociés au sein de l’équipe de ...